2020
DOI: 10.21203/rs.3.rs-56692/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flow Cytometric Analysis of T Lymphocytes and Cytokines in Aqueous Humor of Patients with Varicella Zoster Virus-mediated Acute Retinal Necrosis

Abstract: Background: The purpose of this study is to investigate the aqueous humor (AH) T lymphocyte subsets and cytokines of acute retinal necrosis (ARN) to elucidate the immunologic inflammatory features of this disorder.Methods: Three patients with ARN infected with varicella zoster virus (VZV) who underwent multiple intravitreal injections of ganciclovir were enrolled in this study. The control group consisted of four non-viral infectious patients with acute anterior uveitis (AAU). Flow cytometric analysis was perf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…[36,37] Killer cell lectin-like receptor B1 (KLRB1; CD161) is expressed in NK cells, CD4 + and CD8 + T cell subsets, and NKT cells [38] and it is correlated with uveitis. [39] Bioinformatics analysis revealed that KLRB1 expression is also significantly upregulated in AS. [40] Therefore, we inferred that high KLRB1 levels during AS might increase the risk of NIU.…”
Section: Discussionmentioning
confidence: 99%
“…[36,37] Killer cell lectin-like receptor B1 (KLRB1; CD161) is expressed in NK cells, CD4 + and CD8 + T cell subsets, and NKT cells [38] and it is correlated with uveitis. [39] Bioinformatics analysis revealed that KLRB1 expression is also significantly upregulated in AS. [40] Therefore, we inferred that high KLRB1 levels during AS might increase the risk of NIU.…”
Section: Discussionmentioning
confidence: 99%